Concussion in motor sports: an investigation of an education programme to enhance knowledge, perceptions and attitudes - Adams, Stephanie Alexandra (The University of Edinburgh, 2019)
This thesis investigated knowledge about, and attitudes towards, concussion within the context of four-wheeled motorsport in the United Kingdom. Concussion in sport remains a concern globally. There is evidence to suggest incidence of the injury is high, and rising in motorsport. Despite facing similar challenges to other sports such as rugby or American football, there is a lack of motorsport-specific research. Expert opinion/consensus recommends the importance of increasing knowledge and awareness of concussion, and the need for concussion education programmes that lead to long-term improvements in knowledge as well as attitudes. Furthermore, understanding the context and needs within motorsport are essential to progress in this area. This research used an exploratory mixed-methods design comprised of three studies. First, a feasibility interview study (Study 1) was conducted with key stakeholders (medical personnel, drivers), which sought to understand the context of concussion within motorsport. This informed the need to assess knowledge and attitudes (Study 2) of both medical personnel and drivers, which was conducted using a quantitative online survey. Together, these studies formed the bases for developing, implementing and assessing the first evidence based motorsport-specific concussion education programme (Study 3), delivered in the form of a series of workshops for young drivers. Study 3 employed both quantitative and qualitative methods throughout the design. Findings indicated that concussion is a concern within motorsport and that medical personnel and drivers lack knowledge and awareness about key aspects of the injury. Education and training were the top priority areas for both stakeholder groups. A motorsport-specific education programme, which uniquely explored the potential role of Need for Cognition (NfC), leads to improved knowledge and awareness of concussion in drivers. Furthermore, whilst quantitative data provided limited support of improvements in attitude, qualitative findings did provide examples of improvements in attitude towards the injury. This research makes a substantial contribution towards understanding concussion in motorsport from a psychological and educational perspective. It also contributes to the improvement of concussion education programmes across sport.
Keywords: concussion; motorsport; motor sport; attitudes; knowledge; education; training; brain injury; sport; medical personnel; athlete; mixed-methods